Multi‐MeV electron loss in the heart of the radiation belts. Issue 3 (6th February 2017) - Shprits, Yuri Y.; Kellerman, Adam; Aseev, Nikita; Drozdov, Alexander Y.; Michaelis, Ingo
Abstract: Significant progress has been made in recent years in understanding acceleration mechanisms in the Earth's radiation belts. In particular, a number of studies demonstrated the importance of the local acceleration by analyzing the radial profiles of phase space density (PSD) and observing building up peaks in PSD. In this study, we focus on understanding of the local loss using very similar tools. The profiles of PSD for various values of the first adiabatic invariants during the previously studied 17 January 2013 storm are presented and discussed. The profiles of PSD show clear deepening minimums consistent with the scattering by electromagnetic ion cyclotron waves. Long‐term evolution shows that local minimums in PSD can persist for relatively long times. During considered interval of time the deepening minimums were observed around L * = 4 during 17 January 2013 storm and around L * = 3.5 during 1 March 2013 storm. This study shows a new method that can help identify the location, magnitude, and time of the local loss and will help quantify local loss in the future. This study also provides additional clear and definitive evidence that local loss plays a major role for the dynamics of the multi‐MeV electrons. Key Points: Deepening minimums in PSD at ultra‐relativistic energies show that these particles are subject to local loss Profiles of PSD at relativistic energies are monotonic, as they are not significantly affected by EMIC wave loss Deepening of minimums can be often observed at various radial distances